Prediction of thrombus resolution after intravenous thrombolysis assessed by CT-based thrombus imaging - Nam, Hyo Suk; Kim, Eung Yeop; Kim, Seo Hyun; Kim, Young Dae; Kim, Jinkwon; Lee, Hye Sun; Nam, Chung Mo; Heo, Ji Hoe (Thrombosis and Haemostasis, 2012)
The degree of thrombus resolution directly indicates the effectiveness of a thrombolytic drug. We investigated the degree of thrombus resolution and factors associated with thrombus resolution after intravenous (IV) recombinant tissue plasminogen activator (rt-PA) using thin-section noncontrast computed tomography (NCT). Thin-section NCTs were performed before and immediately after IV rt-PA infusion in acute stroke patients. The thrombus volume and Hounsfield unit were measured using three-dimensional imaging software. Immediate recanalisation was assessed immediately after IV rt-PA infusion using CT angiography. During a three-year study period, 130 patients were prospectively enrolled. On baseline thin-section NCT, no thrombi were found in 30 patients (23%). Among the 100 patients with confirmed thrombus, the median volume decreased by 20% on the follow-up NCT. The thrombus was completely resolved in 8%. Of note, an increase in thrombus volume was observed in 20 patients. Independent predictors of thrombus resolution were total rt-PA dose, thrombus location in the M2 segment of the middle cerebral artery, and time from baseline to follow-up NCT. Thrombus resolution increased by 9% per each 10-mg increase in rt-PA (p = 0.045). Immediate complete recanalisation was achieved in 12% of patients. Total dose of rt-PA was independently associated with complete recanalisation [odds ratio [OR] 4.52, 95% confidence interval [CI] 1.345–15.184) and good functional outcome at three months (modified Rankin scale score <3, OR 2.34, 95% CI 1.104–4.962). In conclusion, rt-PA dose was associated with the degree of thrombus resolution, immediate complete recanalisation, and good outcome at three months. CT-based thrombus imaging may be helpful in determining thrombolysis effectiveness.
Keywords: Computed tomography; thrombus; thrombolytic therapy; cerebrovascular disease